Computational analysis of image‐based drug profiling predicts synergistic drug combinations: Applications in triple‐negative breast cancer. Issue 8 (19th June 2014) - Brandl, Miriam B.; Pasquier, Eddy; Li, Fuhai; Beck, Dominik; Zhang, Sufang; Zhao, Hong; Kavallaris, Maria; Wong, Stephen T.C.
Abstract : An imaged‐based profiling and analysis system was developed to predict clinically effective synergistic drug combinations that could accelerate the identification of effective multi‐drug therapies for the treatment of triple‐negative breast cancer and other challenging malignancies. The identification of effective drug combinations for the treatment of triple‐negative breast cancer (TNBC) was achieved by integrating high‐content screening, computational analysis, and experimental biology. The approach was based on altered cellular phenotypes induced by 55 FDA‐approved drugs and biologically active compounds, acquired using fluorescence microscopy and retained in multivariate compound profiles. Dissimilarities between compound profiles guided the identification of 5 combinations, which were assessed for qualitative interaction on TNBC cell growth. The combination of the microtubule‐targeting drug vinblastine with KSP/Eg5 motor protein inhibitors monastrol or ispinesib showed potent synergism in 3 independent TNBC cell lines, which was not substantiated in normal fibroblasts. The synergistic interaction was mediated by an increase in mitotic arrest with cells demonstrating typical ispinesib‐induced monopolar mitotic spindles, which translated into enhanced apoptosis induction. The antitumour activity of the combination vinblastine/ispinesib was confirmed in an orthotopic mouse model of TNBC. Compared to single drug treatment, combination treatment significantly reduced tumour growth without causing increased toxicity. Image‐based profiling and analysis led to the rapid discovery of a drug combination effective against TNBC in vitro and in vivo, and has the potential to lead to the development of new therapeutic options in other hard‐to‐treat cancers. Highlights: Image‐based profiling identified effective drug combinations in triple negative breast cancer. Combination of KSP/Eg5 inhibitors and vinblastine synergistically inhibited TNBC cell growth. Synergism of combination was mediated by enhanced mitotic arrest and apoptotic cell death. KSP/Eg5 inhibitor with vinblastine increased antitumour activity in a TNBC orthotopic model.